Representasi Qs. Al-Imran: 104 “Analisis atas Nilai Amar Ma’ruf Nahi Munkar dalam Konten Video Tiktok (VT) Dakwah Muezza” - Ali, Firman (STAI Darul Kamal NW Kembang Kerang, 2023)
In today's modern world, humans really need technology to get information and make work easier. Islam as the majority religion, especially in Indonesia, must be able to keep up with the times in spreading its sharia. This study discusses the representation of the values ​​of the Qur'an in the Tiktok dakwahmuezza content. Dakwahmuezza carries a new method of spreading the message of the Qur'an, and the method used is in the form of an animated video. The purpose of this study is to explore the representation of Qs values. Al-Imran: 104 using Stuar Hall's representation theory. The method used in this study is the library research method, with the data needed, namely relevant literature, both books, journals, magazines and so on. The results obtained in this study are that the dakwahmuezza account uses the video animation method in conveying Islamic da'wah messages, so that the content contained in dakwahmuezza already represents the value in Qs. Al-Imran: 104, where the meaning of the verse is presented and discussed in an animated video.